ANALISIS TERHADAP KESIAPAN FINANSIAL SEBELUM MENIKAH STUDI KASUS PADA MAHASISWA STDI IMAM SYAFI’I JEMBER - Abdul Munir; M. Hafid Mahmudi (USRAH: Jurnal Hukum Keluarga Islam, 2025)
Financial readiness before marriage is a crucial aspect that is often overlooked by prospective couples, particularly among university students. Many assume that economic issues can be resolved after marriage, whereas financial problems are in fact one of the main triggers of conflict in household life. A lack of preparedness in dealing with household financial needs can lead to stress, arguments, and even divorce. Therefore, understanding and preparing financially before marriage is essential to building a stable and harmonious family. This study aims to examine the financial readiness of students at STDI Imam Syafi’i Jember in facing marriage through a case study approach. This research uses a qualitative method with a case study approach. The results of the study show that: (1) there are two levels of financial readiness before marriage, namely: (a) Ready-for-marriage level, which includes three contributing factors, and (b) Not-yet-ready-for-marriage level, which also includes three contributing factors; (2) there are seven strategies applied by STDI Imam Syafi’i Jember students to prepare for financial aspects prior to marriage.